Quantification of sericin extracted from different seri bio-waste sources - Qadir, Jasmeena; Islam, Tajamul; Gupta, Rakesh Kumar; Bali, Kamlesh; Sharma, Magdeshwar; Gupta, S. K.; Samnotra, R. K. (Journal of Scientific Agriculture, 2025)
Apart from good quality cocoons, the cocoon crop generates defective cocoons viz., double cocoons, stained cocoons, deformed cocoons, thin end cocoon, cut cocoon, flimsy cocoon, etc., which are non-reliable. Since many cocoons which do not adhere to quality are wasted in this activity, one of the foremost and convenient options is the extraction of sericin from waste cocoons. Sericin is a globular protein possessing promising attributes such as, antioxidant activity, antimicrobial activity, easy absorption and release of moisture, coagulant activity, chemo-protection and protection of solar ultraviolet (UV) radiations. The deformed cocoons, stained cocoons, undersized cocoons and silk floss were used to extract sericin via., hydrothermal degumming using an autoclave. Significantly, the higher quantity of sericin (18.38%) was obtained from deformed cocoons followed by stained cocoons (17.26%), undersized cocoons (15.04%) and floss (13.84%). Following the protocol developed for the extraction of sericin, it is estimated that in J&K, 22.34 MT of sericin could be extracted annually that can contribute to value addition in sericulture.